Safety evaluation of Acalypha wilkesiana in albino rats and BHK-21 cell line. (May 2016) - Makoshi, M.; Oladipo, O.; Gotep, J.; Forcados, G.; Shu, M.; Chinyere, C.; Yusuf, H.; Akanbi, B.; Samuel, A.; Ozele, N.; Dogonyaro, B.; Atiku, A.; et al.
Abstract Acalypha wilkesiana is a member of the spurge family, genusAcalypha, that is widely used in folklore medicine. The aim of this study was to screen aqueous leaf extract ofA. wilkesiana for toxic effects in vitro and in vivo. We examined the phytochemical profile, cytotoxic effects on baby hamster kidney cell line (BHK-21), and oral subacute toxicity ofA. wilkesiana leaf decoction in rats. Rats were given 0, 300, 600, and 1200 mg/kg body weight ofA. wilkesiana leaf extract, daily, orally for 14 days. The phytochemical profile showed the presence of flavonoids, saponin, cardiac glycosides, and tannins. It caused apoptosis in BHK-21 cell line at concentrations of 0, 25, 50, 100, and 200 μg/ml. There was significant increase in the levels of serum AST, ALT, creatinine, urea, Na+, K+, and Cl− levels in all the test groups compared to the control. Histology of the liver revealed centrilobular degeneration and necrosis with sinusoidal dilatation as well as polymorphonuclear and mononuclear infiltration. The kidney showed severe glomerular and tubular degeneration and necrosis with hemorrhage at all doses administered. We conclude that the plant was toxic at the doses tested in vitro and in vivo, and care should be exercised in its use in herbal medicine.